Integrating Payment Systems with Social Features: Post-Voucher War Strategies for E-Commerce Sustainability - Rolando, Benediktus (Forum Kerjasama Pendidikan Tinggi, 2025)
The Indonesian e-commerce landscape has experienced unprecedented growth, reaching USD 62 billion in gross merchandise value in 2023, yet platforms struggle with sustainability, as evidenced by Bukalapak's exit from the marketplace segment in early 2025 despite substantial technological investments. This research investigates how social commerce features, personalization, and payment convenience influence purchase decisions in e-commerce platforms, with vouchers serving as a mediating variable. The study addresses a critical gap in understanding how platform features, and promotional tools interact to drive purchase decisions in emerging markets, particularly in Indonesia's highly competitive e-commerce sector where platforms engage in intense